Perancangan komponen aksesori anting dan kalung dari material sampah plastik - Antonio Junico Da Cruz Soares; Hanif Azhar; Fajar Sadika; Naufal Ary; Tasya Natalia Wijaya; Devi Eka Agustin (Institut Seni Indonesia Yogyakarta, 2023)
The reuse of plastic waste for earrings and necklace accessories is one of the many waste handling options that have been completed by previous experts. Bank sampah bersinar Baleendah (BSB) is an association that often thinks about climate by collecting, organizing, measuring, and providing plastic waste to the authorities or the industry handling plastic waste so that it can be recycled. Repurposing plastic waste becomes an extra style. and the accessory components of earrings and necklaces are the goal of the Bank sampah bersinar Baleendah (BSB) because they see the great potential they have. Therefore, researchers analyzing waste banks agreed to make additional styles, recycling, and accessories, which can later be applied to Bank Sampah bersinar Beleendah (BSB) with data search methods, namely interviews and direct observation as well as special methods in working on designs with experimental methods with simple tools at home. The results of this study will be a spelt for the Bank sampah bersinar Baleendah (BSB) to the community in the use of plastic waste recycling so that the community processes plastic waste independently.